Preliminary insights into cardiopulmonary reserve and hemodynamic stability: exploring submaximal cardiopulmonary exercise testing parameters as potential predictors of intraoperative hemodynamic instability - Agarkov, Daniel; Carr, Zyad J. (Frontiers in Anesthesiology, 2025)
BackgroundIntraoperative hypotension (IOH) is associated with serious adverse outcomes after noncardiac surgery. Preoperative predictors of IOH remain poorly characterized. Intraoperative hemodynamic instability is strongly associated with IOH. The authors hypothesized that submaximal cardiopulmonary exercise testing (smCPET) measures of forced vital capacity (FVC) and gas-exchange derived pulmonary capacitance to peak oxygen uptake slope (GXCAP-VO2) would be associated with two measures of intraoperative hemodynamic instability: intraoperative vasopressor use and systolic average real variability (ARV), respectively.MethodsThis secondary analysis of a feasibility study included adults >60 years undergoing elective noncardiac surgery and completed preoperative smCPET. Multiple cardiopulmonary measures, including FVC, peak oxygen uptake (VO2) and GXCAP-VO2 slope were collected. The primary outcome of intraoperative vasopressor use, and secondary outcome of ARV were tested with multivariable logistic regression and generalized linear models to assess associations supported by decision boundary and mediation analysis.ResultsAmong 101 participants, 54 had measured FVC (median 2.56 L) and 101 had measured GXCAP-VO2 slope (median 29.8). After adjustment, each standard deviation increase in FVC (0.89 L) was associated with halved odds of vasopressor use [2.47 L (SD 0.88) vs. 2.9 L (SD 0.86) adjusted Odds Ratio: 0.496 (95% CI: 0.25–1.01) p = 0.052]. Participants with FVC <2.18 L and surgery duration >152 min had the highest risk of vasopressor use. Systolic ARV was negatively associated with increasing surgical time (p < 0.001). For each 10-unit increase in GXCAP-VO2 slope, systolic ARV is expected to decrease by 9.8% [incidence rate ratio = 0.902, 95% CI (0.84, 0.97)].ConclusionLower measured FVC and GXCAP-VO2 slope were associated with measures of intraoperative hemodynamic instability in older adults undergoing noncardiac surgery. Preoperative assessment of pulmonary function and cardiopulmonary reserve may identify patients at higher risk for intraoperative hemodynamic instability. These exploratory observations establish a foundation for future research on smCPET measures for the prediction of perioperative complications, recognizing intraoperative hemodynamic instability as a complex interplay of patient, anesthetic, and surgical factors.